PENGARUH REWARD DAN PUNISHMENT TERHADAP MOTIVASI KERJA GURU DI SD ISLAM AL-JAMAL KOTA TASIKMALAYA - Siska Auliah Rohmah; Ai Hilyatul Halimah; Wartim (Institut Nahdlatul Ulama Tasikmalaya, 2022)
The existence of an educational institution is inseparable from the element of human resources in it. Human resources are the key to the success of the Institution; therefore, efforts are needed to motivate quality, professional and loyal human resources, among the efforts that must be made through the application of rewards and punishments. The purpose of the research here is to find out reward and punishment, to find out the teacher's work motivation, and to find out how much influence reward and punishment has on teacher work motivation. The method used is a survey method with a quantitative approach with a sample of 20 elementary school teachers through a questionnaire. The results of the descriptive analysis illustrate that most respondents stated that the reward at Al-Jamal Islamic Elementary School, Tasikmalaya City was very good (65%) and most respondents stated that the punishment at Al-Jamal Islamic Elementary School was good (65%) and most respondents stated that the teacher's work motivation at SD Islam Al-Jamal is good (55%). The reward has a positive and significant effect on teacher work motivation with r count for the reward of 0.650 (65%) and r table 0.468 with α 5% indicating that the effect of reward is strong. Meanwhile, punishment obtained r count of -0.269 (-26.9%) and r table 0.468 with α 5% indicating that punishment is very negative. Meanwhile, both reward and punishment have had an impact on the work motivation of teachers at SD Islam Al-Jamal Tasikmalaya by 32.1%. The implications for educational institutions, the application of reward and punishment will be able to create good work motivation and organizational climate.